Bell's Inequalities, Superquantum Correlations, and String Theory - Lay Nam Chang; Zachary Lewis; Djordje Minic; Tatsu Takeuchi; Chia-Hsiung Tze (Advances in High Energy Physics)
We offer an interpretation of superquantum correlations in terms of a “doubly” quantum theory. We argue that string theory, viewed as a quantum theory with two deformation parameters, the string tension α ' , and the string coupling constant